Kitchen and bath laminate countertops 101 [videorecording (DVD)] : with Douglas Smith - Smith, Douglas (Illustrator) (Countertops Revealed, 2005)
Shows how to cut, build, complete the fine finish work, and install both postform and square edge laminate countertops. Highlights the basic and practical as well as the unique and extraordinary.